ADAB, AUTHORITY, AND MOTIVATION IN ISLAMIC EDUCATION: MUSLIM AND WESTERN HADITH PERSPECTIVES ON PESANTREN PEDAGOGY - Yusufi, Adnan; Bani Syarif Maula (Jurnal Tawadhu, 2025)
Research on hadith pedagogy has largely emphasized textual authentication, with limited comparative mapping across Muslim and Western traditions and insufficient attention to pesantren contexts. This article examines three key pedagogical hadiths: the scholars are heirs of the prophets; teacher–student adab; and motivation to acquire knowledge. Muslim perspectives range from the classical to the contemporary, and Western approaches make use of historical-critical methods as well as philological and sociological. The analysis identifies convergence in moral formation and teacher authority, and divergence between authenticity-first and context-first approaches. Muslim scholarship foregrounds isnād and matn criticism together with theological legitimacy, while Western scholarship highlights social context, institutional authority, and cultural practice. Building on these insights, the study proposes a hybrid methodological framework that combines isnād and matn analysis, semantic tracking, and classroom ethnography with psychological measures of motivation. This framework operationalizes hadith pedagogy in pesantren by integrating theological, social, and psychological dimensions, offering a comprehensive approach to strengthening intellectual development, moral guidance, and learner motivation in Islamic education.